Sex-Related Differences in Inflammatory and Immune Activation Markers Before and After Combined Antiretroviral Therapy Initiation. (1st October 2016) - Mathad, Jyoti S.; Gupte, Nikhil; Balagopal, Ashwin; Asmuth, David; Hakim, James; Santos, Breno; Riviere, Cynthia; Hosseinipour, Mina; Sugandhavesa, Patcharaphan; Infante, Rosa; Pillay, Sandy; Cardoso, Sandra W.; et al.
Abstract : Background: Women progress to death at the same rate as men despite lower plasma HIV RNA (viral load). We investigated sex-specific differences in immune activation and inflammation as a potential explanation. Methods: Inflammatory and immune activation markers [interferon γ, tumor necrosis factor (TNF) α, IL-6, IL-18, IFN-γ–induced protein 10, C-reactive protein (CRP), lipopolysaccharide, and sCD14] were measured at weeks 0, 24, and 48 after combination antiretroviral therapy (cART) in a random subcohort (n = 215) who achieved virologic suppression in ACTG A5175 (Prospective Evaluation of Antiretrovirals in Resource-Limited Settings). Association between sex and changes in markers post-cART was examined using random effects models. Average marker differences and 95% confidence intervals were estimated using multivariable models. Results: At baseline, women had lower median log10 viral load (4.93 vs 5.18 copies per milliliter, P = 0.01), CRP (2.32 vs 4.62 mg/L, P = 0.01), detectable lipopolysaccharide (39% vs 55%, P = 0.04), and sCD14 (1.9 vs 2.3 µg/mL, P = 0.06) vs men. By week 48, women had higher interferon γ (22.4 vs 14.9 pg/mL, P = 0.05), TNF-α (11.5 vs 9.5 pg/mL, P = 0.02), and CD4 (373 vs 323 cells per cubic millimeter, P = 0.02). In multivariate analysis, women had greater increases in CD4 and TNF-α but less of a decrease in CRP and sCD14 compared with men. Conclusions: With cART-induced viral suppression, women have less reduction in key markers of inflammation and immune activation compared with men. Future studies should investigate the impact of these sex-specific differences on morbidity and mortality. Abstract : Supplemental Digital Content Is Available in the Text.